An Empirical Method of Estimating Soil Thermal Inertia. (27th July 2015) - Tian, Jing; Su, Hongbo; He, Honglin; Sun, Xiaomin
Abstract : A method of estimating soil thermal inertia (STI), which uses midday soil heat flux (G m ) and diurnal surface temperature amplitude as the inputs, is presented in the paper. G m is achieved from an empirical relationship between net radiation (Rn) and soil heat flux (G ). To validate the STI method, a method proposed by Verhoef, which requires STI and a Fourier series analysis on surface temperature, is used to estimate diurnal G . By comparing diurnal G estimates and diurnal G measurements, the STI method is evaluated indirectly. The results show that the diurnal curve of G estimates can coincide with that of G measurements for bare soil, with the correlation coefficient (R 2 ) of 0.64, bias of 10.1 W·m −2, and root mean squared errors (RMSE) of 40.9 W·m −2 . For the vegetated surface, R 2 is 0.56, bias is −11.9 W·m −2, and RMSE is 49.2 W·m −2 . The large uncertainty in the estimation of G m resulting from the wider variation of the empirical relationship between Rn and G and the difference between mixed surface temperature and soil surface temperature may be the two primary factors for the larger deviation of the diurnal shape and the magnitude between G estimates and G measurements for the vegetated surface.